A Review of the Distribution, Pathogenesis, Virulence Determinants, Epidemiology, and Antibiotic Resistance of Vibrio Parahaemolyticus (Eurasian Medical Research Periodical, 2023)
Vibrio parahaemolyticus is a halophilic, Gram-negative microorganism that creates capsules with somatic (O) and capsular (K) antigens, intake of raw or undercooked seafood spreads virulent V. parahaemolyticus strains that result in severe gastrointestinal illness. V. parahaemolyticus can attach to a variety of host cells, comprising fibroblasts, epithelial cells, and macrophages. In addition to the ability of each clinical strain of V. parahaemolyticus to generate thermostable direct hemolysin (TDH), a substance that has the ability to lyse red blood cells on Wagatsuma blood agar. Among the key factor contributing to the formation as well as the widespread adoption of multidrug resistance (MDR) in V. parahaemolyticus isolates is most likely the wide utilize and abuse of prophylactic antibiotics in aquaculture for the bacterial infection reduction and the quick extension of infection. To summarize an important public health concern is the persistent rise in antibiotic- and drug-resistant strains of V. parahaemolyticus. However, it is crucial to learn more about current antimicrobial trends